2021
DOI: 10.3390/molecules26113328
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization and Bioactivity of Asparagus acutifolius: A Focus on Antioxidant, Cytotoxic, Lipase Inhibitory and Antimicrobial Activities

Abstract: The phytochemical composition of leaves, stems, pericarps and rhizomes ethanolic extracts of Asparagus acutifolius were characterized by HPLC-DAD-MS. A. acutifolius samples contain at least eleven simple phenolics, one flavonon, two flavonols and six steroidal saponins. The stem extracts showed the highest total phenolic acid and flavonoid contents, where cafeic acid and rutin were the main compounds. No flavonoids were detected in the leaf, pericarp or rhizome while caffeic acid and ferulic acid were the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Studies have found that it can reduce the risk of cardiovascular and cerebrovascular diseases such as cancer and high blood pressure [ 26 , 27 , 28 , 29 , 30 ]. Asparagus is a vegetable in daily diet and has potential to develop functional products [ 31 ]. Therefore, understanding the metal contents, pollution levels, and health risks in asparagus and soil is of great significance to ensure the ecological safety of soil, the planting and consumption safety of asparagus, and ultimately the economic benefits of asparagus in Chongming area.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that it can reduce the risk of cardiovascular and cerebrovascular diseases such as cancer and high blood pressure [ 26 , 27 , 28 , 29 , 30 ]. Asparagus is a vegetable in daily diet and has potential to develop functional products [ 31 ]. Therefore, understanding the metal contents, pollution levels, and health risks in asparagus and soil is of great significance to ensure the ecological safety of soil, the planting and consumption safety of asparagus, and ultimately the economic benefits of asparagus in Chongming area.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicated that saponins especially those with steroidal nucleus, flavonoid, and phenols are among the major constituents isolated from the genus Asparagus. Several other minor classes such as alkaloids, tannins, minerals, and amino acids were also reported from Asparagus species [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the aqueous extract was more effective against A. niger and C. albicans. Hamdi et al 25 studied the phytochemical composition and antimicrobial activity of different parts of Asparagus acutifolius and came to the conclusion that the extract from the leaves of the plant was more effective.…”
Section: Edible Plantsmentioning
confidence: 99%